2018
DOI: 10.1080/08958378.2018.1483984
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhalation of ozone induces DNA methylation of apelin in lungs of Long-Evans rats

Abstract: Apelin has cardiopulmonary protective properties that promote vasodilation and maintenance of the endothelial barrier. While reductions in apelin have been identified as a contributor to various lung diseases, including pulmonary edema, its role in the effect of air pollutants has not been examined. Thus, in the current study, we sought to investigate if apelin is a downstream target of inhaled ozone and if such change in expression is related to altered DNA methylation in the lung. Male, Long-Evans rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…These complex ventilatory changes may reflect superimposed changes in ventilatory drive and/or airway obstruction secondary to airway injury that likely developed as a result of the combined drug treatment and repeated ozone exposures. In case of ozone which causes small airway injury, Penh increases correlate with pulmonary protein leakage (Miller et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These complex ventilatory changes may reflect superimposed changes in ventilatory drive and/or airway obstruction secondary to airway injury that likely developed as a result of the combined drug treatment and repeated ozone exposures. In case of ozone which causes small airway injury, Penh increases correlate with pulmonary protein leakage (Miller et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Using high-throughput sequencing, Mishra et al [210] found that greater than 10% DNA methylation of the CpG island of the apelin gene, resulting in a 5.9-fold reduction in apelin expression. Rat ozone exposure decreased the DNMT activity, and Dnmt3a/b gene expression increased DNA methylation in the apelin gene promoter and decreased apelin expression [211]. Contrasting findings have also been reported.…”
Section: Exercise Modulates Myokine Expression Via Epigenetic Regulationmentioning
confidence: 75%
“…It only takes 3-4 ppm to reduce all viruses and bacteria [ 57 ], but at 25 ppm, it is a disinfectant, while at 50+ ppm, it sterilizes surfaces. Ozone can damage the lungs when inhaled, a recent study showed in a rat model that increased methylation of the apelin promoter downstream of DNA damages the lungs, causing the development of pulmonary edema [ 58 ].…”
Section: Resultsmentioning
confidence: 99%